STUDENT’S PERCEPTION TOWARDS THE APPROPRIATENESS OF PHRASE- PICTURE-MATCH- ANALYSIS AS INSTRUCTIONAL MATERIAL IN TEACHING SAMPLING TECHNIQUES - Aron, Annallee Q.; Maneja, Jackylyn M. (PEOPLE: International Journal of Social Sciences, 2020)
The senior high teachers on its third year of implementation in the Philippines become more confident on designing an appropriate material to be used as instructional material that aided on the transfer of learning, especially in the line of teaching Practical Research I (Qualitative Research). With the challenges at hand, and the passion to teach, the researchers created an instructional material to easily understand the meaning behind the different sampling techniques. Being aware that most learners are classified as visuals with regards to their preference on learning, the researchers made and designed the Phrase-Picture-Match-Activity (PPMA) to understand the concept involve on the Different Sampling Techniques. To test the appropriateness of each Phrase and Illustrations chosen, the teachers communicated to the learners and coded their responses and come up with better suggestions, to better fit the design suited to the way how they wanted to learn.